Technologies utilised to solve emerging environmental issues - Esmurzaeva Madina; Bagov Artur; Safarov Ildar (BIO Web of Conferences)
The article will look into the obvious issues of the modern days. The state of the environment in modern times is on the brink of an abyss. One can argue that the tendency of degradation is still going up. Although steps are being taken to slow this trend, at least for this decade. In reality, we are far from close. When we want to introduce new technologies to fight an environmental disaster, one needs to understand that the same technology with a positive goal can have another side. Technology is in the first place in terms of environmental pollution. However, they are by no means to blame, as they are guided by a human. Therefore, technology can be used for good, and in the same way, the same technology can be used for harm. The following article aims to identify technologies that are used to solve environmental problems or at least can be used in the future. In addition, this work attempts to outline the essence of the problem, as well as review some of the work done to understand the use of technology.